Avatar - Cameron, James, 1954-; Landau, Jon; Twentieth Century Fox ([Beverly Hills, CA.] : Twentieth Century Fox, 2010)
Jake Sully is a former Marine who uses a wheelchair. But despite his broken body, Jake is still a warrior at heart. He is recruited to travel light years to the human outpost on Pandora, where a corporate consortium is mining a rare mineral that is the key to solving Earth's energy crisis. He is given a mission to infiltrate the Na'vi, who have become a major obstacle to mining the precious ore. But a beautiful Na'vi female, Neytiri, saves Jake's life -- which changes everything
Title from title screen
Music, James Horner ; editor, James Cameron, John Refoua, Stephen Rivkin ; director of photography, Mauro Fiore
Cast: Sam Worthington, Zoë Saldana, Giovanni Ribisi, Michelle Rodriguez, Sigourney Weaver, Stephen Lang
VCD format
Keywords: Human-alien encounters -- Drama; Extraterrestrial beings -- Drama; Life on other planets -- Drama; Pandora (Imaginary place) -- Drama